Strategic framework (2001-2006) (CARDI [St. Augustine]TT, 2000)
Provides elements of the critical issues affecting the sustainability of the Institute. Serves as a mechanism for building stakeholder commitment to CARDI and colloboration among regional players.
Keywords: AGRICULTURAL RESEARCH